Internalisasi Nilai Cinta Kasih Melalui Meditasi Cahaya (Study Kasus Program Meditasi Cahaya di Sai Study Group Mahendradatta) - Ramadi Putra, I Komang (Metta : Jurnal Ilmu Multidisiplin, 2022)
This study aims to find the internalization of the value of loving-kindness through light meditation in the light meditation program at the Sai Study Group Mahendrata. The method used in this research is qualitative with a descriptive approach with the method of determining the informants in this study is purposive sampling. Data collection methods in this study were observation, interviews and documentation studies. The data analysis method in this study uses analysis from Mile and Huberman, namely data collection, data reduction, and data presentation. This study found that light meditation was carried out to develop the value of loving-kindness. Affirmations performed during light meditation are able to develop one's loving-kindness. Light meditation is also able to destroy mental blocks that have been attached to a person.